Introducing Protestant social ethics : foundations in scripture, history, and practice - Matz, Brian J. (Grand Rapids Baker Academic, 2017)
Despite their rich tradition of social concern, Protestants have historically struggled to articulate why, whether, and how to challenge unethical social structures. This book introduces Protestants to the biblical and historical background of Christian social ethics, inviting them to understand the basis for social action and engage with the broader tradition. It embraces and explains long-standing Christian reflection on social ethics and shows how Scripture and Christian history connect to current social justice issues. Each chapter includes learning outcomes and chapter highlights.
Part 1. Social ethics and scripture. The Pentateuch ; Historical, poetical, and wisdom literature ; Prophets ; Jesus in the New Testament ; The early decades of Christianity ; Part 1 summary -- Part 2. Social ethics in Christian history. Late antiquity ; Middle ages ; Reformations era ; Post-reformations era ; Contemporary Catholic social ethics ; Part 2 summary -- Part 3. Principles for Protestant social ethics. Human dignity ; Common good ; Justice ; Solidarity ; Subsidiarity ; Part 3 summary.
Includes indexes.
Includes bibliographical references and index.
Keywords: Ethics in the Bible; Christian ethics; Christian sociology; Protestant churches -- Doctrines; Evangelicalism